FARMERS' GROUP STRATEGIES IN INCREASING PRODUCTION OF PASSING THE CERTIFIED RICE SEED TEST IN DISTRICT BATANG ASAM DISTRICT TANJUNG JABUNG BARAT - Rendra; Jamaludin; Rahmad Nurmansah (Politeknik Pembangunan Pertanian Bogor, 2023)
This research aims to determine the internal and external factors of passing the certified rice seed test and to determine the strategy of farmer groups in increasing production of passing the seed test in Rawa Medang Village, Batang Asam District, West Tanjung Jabung Regency. Sampling was carried out using purposive sampling technique. This research method uses SWOT analysis. Strength factors include high rice seed production, farmer experience, availability of facilities and infrastructure, cohesiveness of management and group members, and supporting land. Weakness factors include minimal capital for farmer groups, technology implementation that is not yet fully used, only producing a few seed varieties, lack of seed storage technology, lack of evaluation. Opportunity factors include government policy in institutional development, government assistance, availability of seed testing centers, demand for rice seeds, marketing cooperation and market reach. Threat factors include unstable rice seed prices, climate change, pests and diseases, long seed testing times and production costs.The results show that the position of the strategy to increase production passing the certified rice seed test is in quadrant I, namely the SO (strength - Opportunities) combination strategy. An aggressive strategy is to take maximum advantage of opportunities. Alternative strategies to improve the irrigation system in the breeding area, increase farming experience, increase the use of facilities and infrastructure, increase the cohesiveness of management and members of farmer groups, increase seed production.